Analisis Dinamika Organisasi Mahasiswa dalam Program Kampus Merdeka (Studi pada Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sumatera Utara) - Muhammad Abduh Farras Gibran Nasution; Randa Putra Kasea Sinaga (Yayasan Literasi Sains Indonesia, 2023)
Organization is a social system that can be easily found regardless of the form, purpose, pattern or scope of the organization. In carrying out its social functions, there is often a change that affects the organizational life or what is commonly called organizational dynamics, changes in the organization are something that cannot be avoided. Like other organizations, Student Organizations are also dynamic with the problems they face, such as the existence of a new policy issued by the Ministry of Education, Culture, Research and Higher Education, namely the Kampus Merdeka Program. This study aims to analyze the dynamics that occur in student organizations in the midst of the Merdeka Campus program based on theories, variables and realities that explain how the dynamics in the body of the student organization are. This research itself was carried out at the USU's FISIP. This research is a qualitative type with data collection techniques in the research carried out by combining (triangulation) from the process of in-depth interviews, observation and documentation. Then the data will be analyzed by researchers qualitatively and end with conclusions drawn from the results of the research that has been done. Based on the results of the research, the authors found that student organizations at USU's FISIP also dynamically followed the implementation of the Kampus Merdeka program. In the discussion, the researcher found that currently many programs and activities from student organizations were not carried out due to the large number of administrators participating in the independent campus program. has begun to decrease along with the implementation of the Kampus Merdeka program.